Local application of silver nitrate as an adjuvant treatment before deep lamellar keratoplasty for fungal keratitis poorly responsive to medical treatment - Ding, Gang; Gao, Xin; Tan, Yue; Hao, Zhongkai; Wang, Ximing; Zhang, Chenming; Deng, Aijun (Frontiers in Medicine, 2024)
To evaluate the efficacy and safety of local application of silver nitrate (LASN) as an adjuvant treatment before Deep Lamellar Keratoplasty (DLKP) for fungal keratitis responding poorly to medical treatment. A total of 12 patients (12 eyes) with fungal keratitis responding poorly to medical treatment (for at least two weeks) were included. LASN was performed using 2% silver nitrate, the ulcer was cleaned and debrided, and then the silver nitrate cotton stick was applied to the surface of ulcer for a few seconds. The effect of LASN was recorded. The number of hyphae before and after treatment was determined by confocal microscope. After the condition of ulcer improved, DLKP was performed. Fungal recurrence, best corrected visual acuity (BCVA), loose sutures, and endothelial cell count (ECD) were recorded in detail.Clinical resolution of corneal infiltration and edema was observed, and the ulcer boundary became clear in all the 12 patients after 6.91±0.79 days of LASN. Confocal microscopy showed that the number of hyphae was significantly reduced. Ocular pain peaked on day 1 and 2 after treatment, and 9 patients (75%, day 1) and 1 patients (8.3%, day 2) required oral pain medication. During the follow-up period after DLKP, no fungal recurrence and loose suture were observed. After the operation, the BCVA of all patients improved. The mean corneal ECD was 2166.83± 119.75 cells/mm 2 . The LASN is safe, effective and can be well tolerated by patients. Eye pain can be relieved quickly. LASN as an adjuvant treatment before DLKP might be a promising therapeutic strategies.